Development of Teaching Materials for Writing Poetry on the Theme of Local Wisdom in Blitar for Grade VIII Junior High School/MTs Students - Nova Efiana; Ruli Andayani (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2026)
Poetry learning plays an important role in developing creative skills, critical thinking abilities, and instilling cultural values and character. However, observations at MTsN 1 Blitar show that students still have difficulty writing poetry. On the other hand, learning is not yet supported by the use of teaching materials that can stimulate students to create. Therefore, this research and development aims to (1) develop teaching materials for writing poetry with the theme of local wisdom in Blitar for eighth-grade junior high school/MTs students, (2) describe the feasibility test of the teaching materials, and (3) describe the effectiveness test of the developed teaching materials. This research and development was conducted by adapting the ADDIE development model, which consists of four stages, namely analysis, design, development, and implementation. Meanwhile, data analysis was conducted qualitatively and quantitatively. Based on the validation results, the feasibility of the teaching materials reached 94%, which means that they are very feasible, while the student response was 93%, which means that they were well received. Meanwhile, the average N-Gain score was 0.80, which means that there was a high increase in learning outcomes after using these teaching materials, and the N-Gain percentage reached 80.38%, which means that the teaching materials are categorized as effective in achieving learning objectives. Thus, it can be said that these teaching materials are very feasible to implement and effective to use in teaching poetry writing in fifth grade.